Plastic adjustments in xylem vessel traits to drought events in three Cedrela species from Peruvian Tropical Andean forests - Rodríguez Ramírez, Ernesto C. (2022)
Cedrela species occur within the Tropical montane cloud forest (TMCF) and rainforest in North America (Mexico), Central and South America. We assessed the hypothesis that functional xylem hydraulic architecture might be influenced by specific climatic variations. We investigated the effect of climate on tree-ring width and vessel traits (diameter, vessel density, vulnerability index and hydraulic diameter) of three relict-endemic and threatened Cedrela species (Cedrela fissilis, C. nebulosa and C. angustifolia) inhabiting Peruvian Tropical Andean cloud forests. All Cedrela species showed a significant reduction in radial growth and adjusted vessel trait linked with temperature, precipitation, and evapotranspiration. Ring-width and vessel traits showed adaptation within Cedrela species, crucial to understanding a rough indication of the plant’s ability to withstand drought-induced embolism or cavitation. Our results provide evidence for hydraulic mechanisms that determine specific wood anatomical functionality to climatic variation and drought responses. Therefore, changing the frequency or intensity of future drought events might exceed the adaptive limits of TMCF tree species, resulting in a substantial reduction of hydraulic functionality in Peruvian Cedrela species.